THE EFFECT OF AUDIT LAG AND AUDIT TENURE ON GOING-CONCERN AUDIT OPINIONS (Empirical Study of Basic Materials Companies Listed on the IDX in 2021-2023) - Ardillah Putra; Ambar Kusumaningsih (Finance : International Journal of Management Finance, 2025)
This study aims to analyze the effect of Audit Lag and Audit Tenure on Going-Concern Audit Opinions in Basic Materials companies listed on the Indonesia Stock Exchange (IDX) in the 2021-2023 period. The study sample of 73 companies was obtained through purposive sampling. The analysis method used was logistic regression with the help of SPSS 25. The results showed that Audit Lag had no significant effect on Going Concern Audit Opinions, while Audit Tenure had a significant effect. Simultaneously, both variables influenced Going Concern Audit Opinions, indicating that the sustainability of the audit opinion is influenced not only by the audit completion time but also by the length of the auditor's relationship with the client.